The Academic Stress of Final-Year Students in Covid-19 Pandemic Era - Syahril - -; Sitti Riadil Janna; Fatimah . (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to reveal the academic stress of final students in the current Covid-19 pandemic era. The research design used a quantitative descriptive survey of 113 students from various universities in Indonesia, including undergraduate (bachelor), master, and doctoral education levels. The research instrument used an academic stress scale developed by the researcher, which consisted of twelve question items. The distribution of the tool was carried out using google forms. The results showed that several factors caused student academic stress. There are cost factors (difficulty paying tuition fees / UKT and demands to return the scholarship), study conditions (difficulty consulting with supervisors/promoters and unable to find references in the library), and personal problems (conflicts with friends or with a partner and less comfortable boarding/house conditions). Student academic stress is the highest experienced by doctoral students compared to undergraduate and master's level students. Online counselling is recommended to help students experiencing academic stress to complete their studies on time.